2020
DOI: 10.3390/genes11101171
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Resources of Olea europaea L. in the Garda Trentino Olive Groves Revealed by Ancient Trees Genotyping and Parentage Analysis of Drupe Embryos

Abstract: The area of the Garda Lake within the Trentino province (north of Italy) is the northernmost part of Europe where the Mediterranean species Olea europaea L. is traditionally cultivated. ‘Casaliva’ is claimed as the main variety traditionally grown in the Garda Trentino area (GT) from which a world renowned niche extra virgin olive oil is produced. Since a dominant presence of ‘Casaliva’ would link the fruit set success and yield to a self-pollination compatibility system, a deep genetic survey of the olive tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…A phenomenon, generally thought to be a consequence of environmental factors interfering with the SI reaction or to result from the action of modifier genes (Busch & Schoen, 2008;Levin, 1996), is reported as 'leaky' SI. As already discussed in Saumitou-Laprade, Vernet, Vekemans, Billiard, et al (2017), it is observed in some olive cultivars like Koroneiki (Marchese et al, 2016) and Casaliva a homonym of Frantoio (Moreno-Sanz et al, 2020). These cultivars belong to a SI group (Table S1) and present a low rate of selfing.…”
Section: Theoretical Predictions and Dsi Effect In Orchardsmentioning
confidence: 63%
“…A phenomenon, generally thought to be a consequence of environmental factors interfering with the SI reaction or to result from the action of modifier genes (Busch & Schoen, 2008;Levin, 1996), is reported as 'leaky' SI. As already discussed in Saumitou-Laprade, Vernet, Vekemans, Billiard, et al (2017), it is observed in some olive cultivars like Koroneiki (Marchese et al, 2016) and Casaliva a homonym of Frantoio (Moreno-Sanz et al, 2020). These cultivars belong to a SI group (Table S1) and present a low rate of selfing.…”
Section: Theoretical Predictions and Dsi Effect In Orchardsmentioning
confidence: 63%
“…In agreement with previous morphological [ 5 , 6 ] and molecular [ 3 , 6 , 16 ] studies, our results revealed that the redundant genotypes corresponded mainly to synonymy cases. In addition, most of them included cultivars from the same country, followed by pairs or groups of cultivars from close neighbouring countries, as previously reported [ 3 , 33 , 34 ]. However, although to a less extent, synonymy cases between cultivars from distant Mediterranean olive growing countries, as well as in the New World, have also been observed [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional olive groves with monumental specimens host a high number of varieties. The importance of this latter genetic resource and the potential it holds for agriculture is also a common element in other European and Mediterranean contexts, as shown by the recent studies on centenary olive trees conducted in several Mediterranean countries [50][51][52][53][54][55]. The cataloging, characterization, and in situ conservation of secular olive trees is, in fact, a priority to safeguard their genetic, natural, and agricultural value and to protect ancient genotypes threatened with extinction [56,57].…”
Section: Discussionmentioning
confidence: 99%